Desmitificando um modelo de desenvolvimento: a formação da sociedade do turismo na periferia do capitalismo - Valduga, Manoela Carrillo (My University, 2014)
The present abstract presents the problem about the tourism society composition in the capitalism sistem. the method of this work is the historical structural dialectics and the categories Ideology, Symbolic Power, Ethnic Identity, Defensible Development, Touristic Region and Touristic System which supported the empiric analysis, characterized as case study. As result, It was noticed that the historical process that form touristy destinations, apparently with success, is resultant from a conjunct of factors, mainly the enterprising of some local businessmen, that released the Touriem development from the sybolic and ideologic imposition of the political and economical prevailing classes.
O presente resumo apresenta a problemática da formação da sociedade do turismo inserida no sistema capitalista de produção. Utilizou-se como metodologia a dialética histórico-estrutural e as categorias de análise foram Ideologia, Poder Simbólico, Identidade Étnica, Desenvolvimento Sustentável, Região Turística e Sistema Turístico, as quais deram suporte à análise empírica, caracterizada como estudo de caso. Como resultado, infere-se que os processos históricos da formação de destinos turísticos, aparentemente de sucesso, são resultantes de um conjunto de fatores, principalmente do empreendedorismo de empresários locais, que desencadearam o desenvolvimento do turismo, às custas ambientais, gerando desigualdade social, a partir da imposição simbólica e ideológica das classes política e economicamente dominantes.
Keywords: Turismo; Sociedade do turismo; Desenvolvimento sustentável; Desenvolvimento empobrecedor; Gramado - RS; Desenvolvimento turístico; Tourism; Tourism society; Defensible development; Development